Activated carbons developed from oil palm fiber for the removal of dyes from dilute aqueous solution / Fairus Muhamad Darus, Rusdin Laiman and Mohd Nizam Yusof - Muhamad Darus, Fairus; Laiman, Rusdin; Yusof, Mohd Nizam (2007)
Activated carbon, prepared from low cost palm oil fiber has been utilized as the adsorbent for the removal of basic dyes from aqueous solution. A basic dye, methylene blue has been used as the adsorbate. Experiments were conducted at different parameters of methylene blue solutions namely, pH, adsorbent dose, initial concentration of dye and contact time. The most effective of color removal was achieved at pH 6 and 7, while the percentage removal increased with the increase in carbon dose. The removal's percentage increased with increasing of initial dye concentration. The adsorption equilibrium for color was reached at 90 minutes of contact time. Results obtained were tested using two most common isotherms which are Langmuir and Freundlich isotherms. The adsorption patterns were found to follow both isotherms. Results indicated that activated carbon prepared from palm oil fiber could be employed as an alternative to commercial activated carbon in wastewater treatment for colour removal.